FORMAT TEOLOGI ISLAM BAGI PENDERITA GANGGUAN JIWA - Nurseri Hasnah Nasution (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2018)
Modernization, industrialization, advancement of science and technology is one of the factors that accelerate the occurrence of social changes (rapid social changes). These changes have implications for ethical and lifestyle values (ethical values and lifestyle) and cause psychosocial changes. For individuals who are not able to adapt or experience self-adjustment disorder (adjustment disorder against psychosocial stressors will decrease the immunity that affects mental disorders, such as stress, anxiety, and depression. To overcome and prevent the occurrence of mental disorders, need a relevant theological format. The style and concept of traditional Islamic theology is a relevant theological alternative in overcoming and preventing mental disorders. The concept of theology is more emphasis on religious activity that is collective. In addition, the concept of theology is relevant to the personality traits and paradigms of mental disorders. These concepts consist of: the position of reason, the function of revelation, the concept of faith, human action, anthropomorphism, beatific vision, the attributes of God, the deeds of God, the power of God, the justice and the word of God. The style and concept of traditional Islamic theology is relevant for people with mental disorders who experience psychosocial stressors. This review revitalizes the thesis of psychiatrists, psychologists and researchers such as APA (The American Psychiatric Association), Lidenthal, Star, Comstock and Partridge, Stack, Stark, Doyle, Rushing, Breault and Barkley, Clinebell, Robbins and Metzner, Zuckerman, Kals, and Ostfield, Larson, Oxman, TIME and CNN magazines, LevinEastern Virginia Medical School, Matthews-George Town University, Harris. The experts stated that psychoreligious is very effective and efficient in overcoming and preventing mental disorders.